(untitled) (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2022)
The purpose of this qualitative descriptive study was to discover the students’ conceptual understanding of Quran-integrated chemistry learning. This study included 37 third-year students from UIN Raden Fatah Palembang. The Grounded Theory design was used for this study. The findings revealed that students’ conceptual understanding was classified into seven categories. As many as 89.19 percent of students have a conceptual understanding dichotomy between religion and chemistry.